Disability progression in relapse-free multiple sclerosis patients on fingolimod versus interferon-beta/glatiramer acetate. (March 2021) - von Wyl, Viktor; Benkert, Pascal; Moser, André; Lorscheider, Johannes; Décard, Bernhard; Hänni, Peter; Lienert, Carmen; Kuhle, Jens; Derfuss, Tobias; Kappos, Ludwig; Yaldizli, Özgür
Background: Disability progression independent of relapses (PIRA) has been described as a frequent phenomenon in relapsing-remitting multiple sclerosis (RRMS). Objective: To compare the occurrence of disability progression in relapse-free RRMS patients on interferon-beta/glatiramer acetate (IFN/GA) versus fingolimod. Methods: This study is based on data from the Swiss association for joint tasks of health insurers. Time to relapse and 12-month confirmed disability progression were compared between treatment groups using multivariable Cox regression analysis with confounder adjustment. Inverse-probability weighting was applied to correct for the bias that patients on fingolimod have a higher chance to remain relapse-free than patients on IFN/GA. Results: We included 1640 patients (64% IFN/GA, 36% fingolimod, median total follow-up time = 4–5 years). Disease-modifying treatment (DMT) groups were well balanced with regard to potential confounders. Disability progression was observed in 155 patients (8.8%) on IFN/GA and 51 (7.6%) on fingolimod, of which 44 and 23 were relapse-free during the initial DMT, respectively. Adjusted standard regression analysis on all patients indicated that those on fingolimod experience less frequently disability progression compared with IFN/GA (hazard ratio = 0.53 (95% confidence interval = 0.37–0.76)). After bias correction, this was also true for patients without relapses (hazard ratio=0.56 (95% confidence interval = 0.32–0.98). Conclusion: Our analysis indicates that fingolimod is superior to IFN/GA in preventing disability progression in both relapsing and relapse-free, young, newly diagnosed RRMS patients.